2015
DOI: 10.1371/journal.pone.0117215
|View full text |Cite
|
Sign up to set email alerts
|

Target Modulation by a Kinase Inhibitor Engineered to Induce a Tandem Blockade of the Epidermal Growth Factor Receptor (EGFR) and c-Src: The Concept of Type III Combi-Targeting

Abstract: Cancer cells are characterized by a complex network of interrelated and compensatory signaling driven by multiple kinases that reduce their sensitivity to targeted therapy. Therefore, strategies directed at inhibiting two or more kinases are required to robustly block the growth of refractory tumour cells. Here we report on a novel strategy to promote sustained inhibition of two oncogenic kinases (Kin-1 and Kin-2) by designing a molecule K1-K2, termed “combi-molecule”, to induce a tandem blockade of Kin-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…With the EGFR-expressing 4T1 tumor model (26), we stratified excised tumors into “low,” “medium,” and “high” antibody groups. Co-injected TNP-encapsulated docetaxel was then quantified.…”
Section: Resultsmentioning
confidence: 99%
“…With the EGFR-expressing 4T1 tumor model (26), we stratified excised tumors into “low,” “medium,” and “high” antibody groups. Co-injected TNP-encapsulated docetaxel was then quantified.…”
Section: Resultsmentioning
confidence: 99%
“… 1 c-Src, a prometastasis oncogene, is well characterized to promote cellular invasion, migration and has been justly proposed as a therapeutic target in cancers. 2 , 3 , 4 , 5 However, the biochemical regulation of c-Src activation is not fully understood. The best-characterized Src regulator is phosphorylation, with the two major sites of phosphorylation on murine and chicken c-Src being Tyr416 (Tyr419 in humans) and Tyr527 (Tyr530 in humans).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that ROCK inhibition by Y-27632 can inhibit the infiltration of MDA-MB-231 cells using 2D in vitro assays 102 104 . Conversely, the EGFR inhibitor Gefitinib has been shown to have potent anti-proliferative effects on MDA-MB-231 cells 105 107 , while the anti-invasive effect is less well established 108 110 . To quantify the changes in invasion depth upon inhibition, invaded MDA-MB-231 cells at each 100 μm increment were divided by the number of cells on the surface of the collagen matrix, in a similar manner to the invasive index calculated in Fig.…”
Section: Resultsmentioning
confidence: 99%